PENINGKATAN KEMAMPUAN KOGNITIF PADA LANSIA MELALUI MEMORY TRAINING DENGAN TEKNIK MNEMONIC - Dyah Herawati, Vitri; Indriyati; Widiyono (P3M Universitas Aisyiyah Surakarta, 2025)
elderly who experience dementia and decreased mental abilities, where there are disturbances in memory, thought, judgment and the ability to focus attention, and personality decline can occur, so that sometimes there are disturbances of the bio-psycho-social-spiritual in the elderly. According to research, the brain of someone who is active (likes to think) will be healthier overall than people who don't or rarely use their brains. In theory, an active organ will require a supply of oxygen and protein. Dementia is a memory function disorder that occurs slowly. Dementia is quite common in the elderly, affecting about 10% of the age group over 65 years and 47% of the age group over 85 years. About 10-20% of dementia cases are reversible or treatable. Decreased ability of the brain and body makes the body easy to fall sick, senile and frustrated. Even so, this decrease can be corrected by doing Memory Training with Mnemonic Techniques. Mnemonic is a special trick that is used as a mental